Transthoracic electrical bioimpedence cardiac output: comparison with multigated equillibrium radionuclide cardiography - Gujjar, Arunodaya R.; Muralidhar, K.; Bhandopadhyaya, Abhijit; Sathyaprabha, T. N.; Janaki, P.; Mahalla, B. K.; Gupta, Ratan; Banakal, Sanjay; Jairaj, P. S. (Journal of clinical monitoring and computing, 2010)
Introduction Thoracic electrical bioimpedance (TEB) for measuring cardiac output (CO) is being explored increasingly as an alternative to pulmonary artery catheter. The major advantage of this technology is that it is non-invasive and easy to perform. Several studies have compared it to thermodilution cardiac output using PA catheter, with variable correlation. Multigated radionuclide equilibrium cardiography (RNEC) method of cardiac output measurement is known to be reliable. Objective To compare cardiac output measured by thoracic electrical bioimpdenace with that measured by multigated radionuclide equilibrium cardiography. Patients and methods CO studies were performed sequentially at a single sitting by TEB and RNEC methods among patients with cardiac symptoms referred for radionuclide study as part of their evaluation. TEB CO was measured by placing two pairs of electrodes on either side of neck and two other pairs on either side of the lower chest. Stroke volume was estimated from the sequential changes in transthoracic electrical bioimpedance induced by rhythmic aortic blood flow, using Kubicek equation. RNEC-CO was measured by intravenous injection of radio-active Technitium-tagged RBCs followed by ECG gated blood pool imaging over the chest (MUGA study). Bland–Altman analysis was used to compare the measurements. Results A total of 32 subjects with proven or suspected ischemic heart disease, but without overt cardiac failure, edema or arrhythmias were studied (M:F::26:6; mean age: 48 ± 12 years). The mean TEB-CO was 3.54 ± 1.052 l/min and mean RNEC-CO was 3.907 ± 0.952 l/min. Correlation coefficient ( r ) for these measurements was 0.67 (p < 0.01), with bias: −0.421 l/min; precision: 1.557 l/min; and percentage error of measurement: 42.35%. Conclusions This study observed a moderate correlation between TEB and RNEC methods of CO measurement. Further studies are indicated to explore the relative utility of TEB in comparison with RNEC as well as other methods of CO measurement before considering its use in patients with ischemic heart disease.